SUSTAINABLE PEST MANAGEMENT SYSTEMS: BALANCING ECOLOGICAL AND ECONOMIC NEEDS IN AGRICULTURE – A REVIEW - MUNEESWARI P,; NANDAGOPAL S,; SONIA R,; LAKSHMANAN R,; RAMESH KUMAR S, (The Bioscan, 2025)
Sustainable pest management is a crucial aspect of modern agriculture, aiming to protect crops while minimizing environmental impact and ensuring economic viability. Traditional pest control methods, primarily relying on chemical pesticides, have raised concerns due to their adverse effects on ecosystems, human health, and biodiversity. This review explores sustainable pest management systems that integrate ecological principles and economic considerations. Approaches such as Integrated Pest Management (IPM), biological control, and the use of eco-friendly pesticides are examined for their effectiveness in reducing pest populations while maintaining environmental balance. The review emphasizes the importance of using diverse strategies tailored to specific agricultural contexts, including crop type, pest species, and local environmental conditions. Additionally, it addresses the economic benefits of sustainable pest management, including cost savings, improved crop yields, and long-term soil health. The paper concludes by highlighting the need for continued research and innovation to develop and implement pest management systems that are both ecologically sound and economically feasible, promoting the long-term sustainability of agricultural practices.